2020
DOI: 10.3389/fmicb.2020.555739
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Is Crucial for the Proliferation of Gut Escherichia coli Caused by H9N2 AIV Infection and Effective Regulation by Chinese Herbal Medicine Ageratum-Liquid

Abstract: H9N2 avian influenza virus (AIV) infection in chickens is often accompanied by secondary bacterial infection, but the mechanism is unclear. The aim of the present study was to reveal that mechanism and explore non-antibiotic treatment. 16s rRNA sequencing and metabonomics were performed in the intestinal contents of chickens infected with H9N2 AIV or H9N2 AIV and fed with ageratum-liquid (AL) to reveal the metabolite that promote intestinal Escherichia coli (E. coli) proliferation caused by H9N2 AIV, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Nitrate metabolism could be used as an index to detect the reproductive level of E. coli in chicken intestinal tract. Previous studies had demonstrated that the level of nitrate metabolism in the intestine was positively correlated with the reproductive level of E. coli ( Zhang et al, 2020b ). In this study, the ileal tissues at the ileocecal junction of chickens in each group were collected for the detection of nitrate content 5 dpc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrate metabolism could be used as an index to detect the reproductive level of E. coli in chicken intestinal tract. Previous studies had demonstrated that the level of nitrate metabolism in the intestine was positively correlated with the reproductive level of E. coli ( Zhang et al, 2020b ). In this study, the ileal tissues at the ileocecal junction of chickens in each group were collected for the detection of nitrate content 5 dpc.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA of the same quality ileal tissue was extracted with TRIzol (Invitrogen, Carlsbad, CA) according to the manufacturer's instructions. The total RNA was reverse transcribed into cDNA using the Genome Removal Reverse Transcription kit (Tiangen, Beijing, China), and gene expression level of ileum was detected using RT-qPCR as described previously ( Table 1 ; Zhang et al, 2020 b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal microbes can be divided into intestinal symbiotic bacteria, conditional pathogenic bacteria, and pathogenic bacteria regarding to the relationship between the intestinal tract and host ( 52 ). The intestinal tract concentrations of conditioned pathogens are low, such as E. coli which is facultative anaerobes, but when intestinal homeostasis is disrupted, for instance, when the body is infected by virus, the proliferation of E. coli is rapidly promoted and led to intestinal disorders ( 53 ). In this study, application of the dietary antimicrobial peptide plectasin can significantly reduce the number of E. coli in the ileum and promote an increase in the content of Lactobacillus in the ileum, illustrating that plectasin can inhibit the proliferation of harmful bacteria in the intestine and change the structure of intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the three major metabolic processes of host cells described above, we found that steroid biosynthesis and nitrogen metabolism were also altered after infection with FAdV-4. These are important host metabolic pathways that control the process and outcome of virus infections ( 49 , 50 ). Further studies on metabolic genes and signaling pathways associated with FAdV-4 infection may provide some reference value for studying the pathogenesis and new diagnostic methods of FAdV-4.…”
Section: Discussionmentioning
confidence: 99%